Strategic application of CuAAC click chemistry in the modification of natural products for anticancer activity - Zaozao Xiao; Yuang Gu; Hewei Dong; Bo Liu; Weiwei Jin; Jie Li; Peixiang Ma; Hongtao Xu; Wei Hou (Elsevier, 2023)
Natural products play a key role in the history of human drug discovery, and especially for the anticancer agents. Copper(I)-catalyzed alkyne-azide [3+2] cycloaddition (CuAAC) reaction is perhaps the most powerful method for the efficient modification of complex natural products, enabling the direct incorporation of various functional groups accompanied by the formation of the multifunctional 1,2,3-triazole motif, which could not only serve as an basic and hydrophilic connecting group but also as a bioisosteres of 5- or 6-membered heterocycles or an amide group, thus facilitating the improvement of anticancer activities and/or drug-like properties. This contribution extensively summarizes the state-of-the-art application of 1,2,3-triazole in the modification of natural products for anticancer activity. The aim is to gain a deep understanding of the fruitful achievements as well as limitations of CuAAC click chemistry in natural product modification for anticancer activity, and provide perspectives and directions regarding future studies in natural product medicinal chemistry.